Effect of Plant Age and Altitude on the Essential Oil Composition of Cinnamomum cullilawan from Maluku, Indonesia - Imanuel Berly Delvis Kapelle; Hanoch Sohilait; Andrianto Pilayate; Nini Munirah Renur (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
Cinnamomum cullilawan Blume from Maluku is a potential source of essential oil for pharmaceutical, cosmetic, food, and natural product-based industries. This study evaluated the effects of plant age and elevation on the yield and chemical composition of C. cullilawan essential oil. Bark samples were collected from four different locations (n = 4), representing plant ages of 8, 10, 15, and 20 years and different elevation gradients. Essential oils were extracted by steam distillation and analyzed using gas chromatography–mass spectrometry (GC–MS). Statistical analyses included linear regression, Analysis of Variance (ANOVA), partial t-test, and Principal Component Analysis (PCA). The essential oil yield ranged from 0.84% to 1.83%, with the highest yield obtained from 20-year-old plants (1.83%). ANOVA showed that plant age and elevation had a significant simultaneous effect on essential oil yield (p = 0.04), with significant partial effects of plant age (p = 0.026) and elevation (p = 0.034). GC–MS analysis revealed that eugenol and linalool were the dominant compounds. The highest eugenol content was found in 8-year-old plants (92.35%), whereas samples from higher elevation showed the highest linalool content (24.45%) and the lowest safrole content (0.76%). Statistical analysis indicated that eugenol (p = 0.03), safrole (p = 0.038), linalool (p = 0.047), and terpineol (p = 0.038) were significantly influenced by plant age and elevation, while other minor compounds showed no significant effect (p > 0.05). PCA showed that the first two principal components accounted for 83.14% of the total variation. These findings indicate that ontogenetic and ecological factors influence essential oil yield and chemical composition and may contribute to shifts in the relative dominance of phenylpropanoid and terpenoid compounds, providing a scientific basis for optimizing cultivation and standardizing C. cullilawan essential oil quality.